2015
DOI: 10.1080/13669877.2014.1003318
|View full text |Cite
|
Sign up to set email alerts
|

Consumers’ avoidance of information on red meat risks: information exposure effects on attitudes and perceived knowledge

Abstract: (2015): Consumers' avoidance of information on red meat risks: information exposure effects on attitudes and perceived knowledge, Journal of Risk Research, DOI: 10.1080/13669877.2014 To link to this article: http://dx.doi.org/10.1080/13669877.2014.1003318 PLEASE SCROLL DOWN FOR ARTICLETaylor & Francis makes every effort to ensure the accuracy of all the information (the "Content") contained in the publications on our platform. However, Taylor & Francis, our agents, and our licensors make no representations or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 39 publications
(48 reference statements)
0
29
0
Order By: Relevance
“…The information consisted of a fact sheet on the impact of meat on the climate, making clear that emissions of greenhouse gases can be reduced by eating less meat and that beef and mutton have significantly higher emissions costs than other meats (see online supplemental material for more details). We used a timer to measure the students' residence time on the page as we expected that the students receiving the information would not be equally motivated to process the information [49,50].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The information consisted of a fact sheet on the impact of meat on the climate, making clear that emissions of greenhouse gases can be reduced by eating less meat and that beef and mutton have significantly higher emissions costs than other meats (see online supplemental material for more details). We used a timer to measure the students' residence time on the page as we expected that the students receiving the information would not be equally motivated to process the information [49,50].…”
Section: Methodsmentioning
confidence: 99%
“…Higher residence times may indicate a higher motivation to process information, while very low residence times may indicate information avoidance. Avoidance of information related to meat issues is not uncommon [36,49,50,55]. Many people have conflicting thoughts about meat: they love eating meat, but they also do not like its harmful impact (e.g., on animal welfare, health or the environment).…”
Section: The Influence Of Information About the Climate Impact Of Meatmentioning
confidence: 99%
“…Cognitive dissonance theory and empirical evidence demonstrated that initial attitudes may moderate the effect of risk–benefit messages (Frewer et al, ; Gaspar et al, ; Narayan et al, ). Distinguishing between initial feelings of dread and optimism, we studied whether this also held for nanodesigned food.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, initial attitudes may affect the impact of the provided information. Cognitive dissonance theory suggests that individuals are likely to stick to their opinions, which might affect the way they seek, process and avoid new information (Deline & Kahlor, 2019;Gaspar et al, 2016;Kuhn, 2000;Narayan, Case, & Edwards, 2011). The empirical evidence on the effects of prior attitude in risk communication is fragmented (Frewer et al, 2016).…”
Section: Potential Moderators: Initial Attitudesmentioning
confidence: 99%
“…Accordingly, it has been demonstrated that some people show a tendency to avoid information that is communicated by health practitioners (Brashers, Goldsmith, & Hsieh, 2002). For example, as shown by Gaspar et al (2015), if an information on risk-benefits (e.g. maximum daily amount of red meat consumption) somewhat contradicts the previous information individual's had, their existing attitudes (e.g.…”
Section: Barriers To Older Adult's Adherence To Recommendationsmentioning
confidence: 99%